A nonsmooth equation system solver based on subgradient method - Long, Q.; Wu, Changzhi (2017)
© 2017 IEEE. In this paper, a subgradient method is developed to solve the system of (nonsmooth) equations. First, the system of (nonsmooth) equations is transformed into a nonsmooth optimization problem with zero minimal objective function value. Then, a subgradient method is applied to solve the nonsmooth optimization problem. During the processes, the pre-known optimal objective function value is adopted to update step sizes. Several numerical experiments show that the proposed method is efficient and robust.